DETERMINATION OF Ni, Pb AND Cu IN PLANT AND SOIL SAMPLES TO MONITOR POLLUTION EXTENT: COMPARISON OF KIRKLARELI-ELAZIG CITIES, TURKEY - Ozcan, Cemile; Yaman, Mehmet (Parlar Scientific Publications (P S P), 2018)
The purpose of this article is to biomonitor the effects of pollution in Pinarhisar, Kirklareli, Turkey using plants. For this purpose, nickel (Ni), lead (Pb) and copper (Cu) concentrations in three plant species were determined by flame atomic absorption spectrometry. These heavy metals are emitted into the environment in various ways such as transportation, industry, fossil fuels, agriculture, and other human activities. The leaves of the Pinus nigra L., Cedrus libani L. and Cupressus arizonica L. together with soil samples were collected from different points depending on the distance from the cement and lime factory and proximity to the city center. These monitoring studies have been carried out to determine the degree of inorganic contamination using these plants. The samples were digested by microwave digestion method. The results of study were compared with the results for the same plant species collected from Elazig city in Turkey. The ranges of heavy metal in the soil of Pinarhisar and Elazig was found as; Ni, 2.7-8.2 mg kg(-1) and 10-35 mg kg(-1); Pb, 2.0-3.5 mg kg(-1) and 6-12 mg kg(-1); Cu, 18-44 mg kg(-1) and 21-38 mg kg(-1), respectively.
Keywords: Plant; soil; Cedrus libani L.; Cupressus arizonica L.; Pinus nigra L.; trace metals